Addition of a Cyclophosphine to Nitriles: An Inorganic Click Reaction Featuring Protio, Organo, and Main‐Group Catalysis. Issue 32 (7th July 2017) - Chitnis, Saurabh S.; Sparkes, Hazel A.; Annibale, Vincent T.; Pridmore, Natalie E.; Oliver, Alex M.; Manners, Ian
Abstract: The addition of a cyclotriphosphine to a broad range of nitriles gives access to the first examples of free 1‐aza‐2, 3, 4‐triphospholenes in a rapid, ambient temperature, one‐pot, high‐yield protocol. The reaction produces electron‐rich heterocycles (four lone pairs) and features homoatomic σ‐bond heterolysis, thereby combining the key features of the 1, 3‐dipolar cycloaddition chemistry of azides and cyclopropanes. Also reported is the first catalytic addition of P−P bonds to the C≡N bond. The coordination chemistry of the new heterocycles is explored. Abstract : Click for P : The catalytic cycloaddition of nitriles to a cyclotriphosphine gives the first examples of free 1‐aza‐2, 3, 4‐triphospholenes. This electrophile‐mediated reaction is rapid (<5 min), and proceeds at ambient temperature in a one‐pot, high‐yield protocol with a broad substrate scope, and represents a phosphorus analogue of the azide–nitrile and cyclopropane–nitrile click [3+2] cycloadditions.